COLLECTIVE IDENTITY AS RESISTANCE(RESPONS TO THE SANTRI REGULATION OF PONDOK PESANTREN MIFTAHUL HUDA) - Juju Saepudin (Pusbindiklat - LIPI, 2011)
Pesantren generally practices regulation for the forming of character and discipline santri. But in reality the institution applying total institution always emerges resistance. This research wanted to know the pattern of covert resistance by santri to order of discipline. The method of collecting data were taken through observation, depth interview, and documentation study. From the result of inductively data analysis, it is known that the resistance pattern of santri who performed in groups provides space of collective identity development. With a collective identity, all santri develop cooperation to protect one another, especially in the framework of tight regulation manage in pesantren.